Measurement of costs of quality in wood plywood production by the ABC (Activity Based Costing) costing method and by Absorption - Rocha Braga, Gustavo Henrique [UNESP]; Cervi, Ricardo Ghantous [UNESP]; Oliveira, Paulo Andre de; Rodrigues, Sergio Augusto [UNESP] (Univ Fed Rural Pernambuco, Dept Administracao, 2020)
One of the main products produced from the Brazilian planted forests are the wooden panels. Due to the high competitiveness of companies in the market and the demand of consumers for quality products, companies need to gain greater control over manufacturing processes as well as the costs of these operations. In this context, adopting a costing method that optimizes cost allocation and provides better information for decision making is essential. This study aimed to analyze the costs of quality control in a wood plywood production company, using the Activity Based Costing (ABC) method, in addition to comparing it with the absorption costing method, which is currently used in the company. With that, a case study was carried out in a company that produces wood plywood, located in the interior of Parana state. Data were collected from primary sources, where observational studies were conducted to analyze the manufacturing processes of the products, as well as the resources consumed for later determination of the costs incurred in the processes of the quality sector. Interviews were also conducted with the company's employees using semi-structured questionnaires, where preestablished questions were prepared, in addition to filling out forms for data recording. With the application of the ABC costing method in the company, it was possible to obtain a precise definition of the cost items that make up its products and to verify that Plasticized plywood accounts for 40.58% of quality costs, C+C 30.48% and CDX 28.94%, whereas by the absorption method the representativity approach would be 33.81%, 11.79% and 54.41%, respectively. Representing an average variation in the cost of quality per product of R$ 2,638.27. It was concluded that the company can improve its decisions with the most effective allocation of indirect costs of quality in its products, thus eliminating distortions in the apportionment basis of the absorption costing method.
Keywords: ABC costing; Plywood panel; Quality